MEASUREMENT OF GULLY EROSION ON FARM ROAD USING PROFILE REDUCED LEVEL METHOD IN ILE-APA, ILORIN-WEST, KWARA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2025)
Farm roads are essential for the conveyance of farm inputs to the farm and evacuation of harvested crops from the farm. Many rural farm roads, including such roads as Ile-Apa  road in Ilorin-East Local Government area of Kwara State, are devasted by erosion thereby hampering trafficability, even by pedestrians, and therefore need urgent attention. Measurement of the extent of the gullies on this road by traditional methods and models may not be adequate due to their nature and time requirement. The Profile Reduced Level method was used to measure the gully on the Ile-Apa farm road as it produced immediate results. Results obtained from the measurement showed that the gully had an average depth of 0.58 ± 0.35 m, which varied from -0.97 m to 0.03 m, and a mean width 2.45 ± 1.05 m. These parameters indicated that trafficability of the road may be impossible owing the varying and undulation of the gully bottom, but may allow for pedestrian passage, though with much discomfort. This may lead to increased hunger and poverty thereby aggravating food insecurity. An urgent stabilisation of the road is therefore recommended.
Keywords: Soil erosion; Farm roads; Gully; Profile reduced levels; Trafficability